The Effect of the Execution of the Sale of the Right Object on the Position of Bank Creditors - Stevani Komara; Habib Adjie (PT Publikasiku Academic Solution, 2023)
The results of this study show that the right of liability is the object of guarantee that is most in demand by creditors (banks) as debt collateral. The value of the rights contained in thecertificate of rights of dependents has an important influence in determining the position of creditors as creditors who have preferential rights or only limited to as a concurrent creditor. If the value of the dependent rights has a greater value than the debtor's debt, then the creditor's position as the holder of the liability right is the preferred creditor, which takes precedence repayment of it than other creditors. However, the determination ofthe creditor's position as a preferred creditor or not can also be viewed from the proceeds of the sale of the object of liability from the results of auction execution. If the selling price of theobject of liability is greater than the debtor's debt, the creditor has the right to take precedence over full repayment by taking the proceeds Net sales are only limited to debtors. Meanwhile, if the proceeds from the sale of the object of liability are smaller than the debtor's debt, then the remaining debt of the debtor positions the creditor as a concurrent creditor meaning that the repayment of the remaining debtor is divided equally with other creditors